Most valued PMO functions in a project-oriented Tech Company prior to PMO set up - Joana Filipe; Domingues, L. (Procedia Computer Science, 2025)
Purpose: Not all organizations have explored the potential of a PMO to support project delivery. We will use the case of an IT Portuguese company that is evolving into a project-oriented set up to ascertain the perceived value of PMO and associated functions. The goal is to tap into the insights provided by leadership, to determine whether a PMO would be suitable for the company, and which PMO design would be likely to respond to the most pressing internal project management challenges. Methodology: a case study methodology was used. Data was collected from observation, questionnaires and a focus group session, directed at the leadership layer of the organization (including top leadership). Findings: a multi-project PMO had not been witnessed often by participants. PMO functions were largely deemed as very important or of considerable importance to the company and were not being adequately compensated by other areas. Control and standardization related functions gathered strong consensus. PMO operational and supportive nature appears to be favored. Research Limitations: more focus group sessions, targeting mid-level management should be held, and are planned, to determine whether the conclusions corroborate the findings. Also, non-management staff were not included in the study. Practical Value: companies without PMO in similar contexts can benefit from the example to support PMO creation process, including PMO design and target approach.